Reading Legislation and Ivor Richardson - McGrath, John (Victoria University of Wellington Law Review, 2002)
In this paper, I endeavor to compare approaches to statutory interpretation in New Zealand in the early 1960s with those prevalent in the year 2000. I do so with particular reference to the judgments of Sir Ivor Richardson who will retire as President of the Court of Appeal of New Zealand on 24 May 2002. At my starting point Sir Ivor was in private practice in Invercargill, but in June 1963 he moved to Wellington and took up a position as Crown Counsel in the Crown Law Office.